Toxicidade aguda do pesticida clorpirifós de formulação comercial em tambaqui (Colossoma macropomum, Cuvier, 1818) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Assessing the toxicity of pesticides used in temporary crops for aquatic organisms allows to elucidate newly installed or aggregated disturbances over time. Thus, this ecotoxicological study aimed to evaluate the acute toxicity of the 48% chlorpyrifos pesticide (Klorpan® 480EC) in order to determine the mean lethal concentration (LC50-96h) for tambaqui (Colossoma macropomum) fingerlings. Toxic sensitivity of the test organism was preliminarily assessed using the reference substance “potassium dichromate”. Acute toxicity tests were performed under controlled laboratory conditions for 96 hours of exposure under static system. The medium weight of juveniles was 1.02 ± 0.06g were distributed in groups (n = 15), formed by triplicates of 5 individuals per aquarium for each concentration of the established lethality range: 2.5, 10, 15, 25 and 45 µg / L, plus one control (white). The lethality data were processed by the Trimmed Spearman-Karber® method, which by Probito analyzes determined the LC50- 96h of 16.42 µg / L of the chlorpyrifos for tambaqui juveniles. Fast and severe effects caused the animals to die within 48h of the test, and behavioral changes were observed up to 96h of exposure. Prior to inducing death in animals, this pesticide caused some behavioral changes at all concentrations, such as: accelerated operculum movement, continuous swimming, surface breathing, loss of swimming balance, erratic swimming, paralysis, spasms, seizures, and others. The Exploratory qualitative / quantitative methodological analyzes of these behavioral effects demonstrated a possible concentration-response relationship. The results suggest that the chlorpyrifos pesticide has been shown to be very toxic to fish, and poses a major threat to the survival of aquatic biota.
Keywords: Farmacologia; Toxicidade; Pesticidas; Avaliação de riscos; Tambaqui (Peixe); Resíduos de Pesticidas em Alimentos; CNPQ::CIÊNCIAS BIOLÓGICA::FARMACOLOGIA::TOXICOLOGIA; FISIOLOGIA AMBIENTAL